Workshop on Steam Learning Strategy Development with Loosparts Media for Kindergarten Teachers - Titik Mulat Widyastuti; Yulian Agus Suminar; Tri Ratna Herawati; Rika Novita Kusumaningrum; Binarsa Binarsa (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This workshop activity aims to assist teachers in developing Steam learning strategies with loose part media for teachers at RA Maarif Candran Godean Yogyakarta Kindergarten. The subjects in this workshop were RA Maarif Candra Kindergarten teachers in Yogyakarta, totaling 11 people. The stages of the work shop carried out are debriefing, mentoring, implementation and evaluation. The result of the workshop implementation was an increase in teachers' knowledge in developing learning strategies for the Steam model with loose parts media as seen from an average pre-test of 10.45 with an initial indication of moderate teachers and an average post-test of 18.02 with an indication of teachers' knowledge in the development of learning strategies for the Steam model and Media Loosepart increased. After participating in the training activities, the level of understanding of teachers increased as seen from the results of observations showing that 91% of teachers were able to design and implement STEAM learning strategies with loosepart media.